In vitro evaluation of antioxidant, anticancer, and antiviral activities of exopolysaccharide from Streptomyces hirsutus NRC2018 - Mohamed E. El Awady, Mohamed A. Nasr Eldin, Heba M. Ibrahim , Mohamed E. Al Bahnasy, Samir H. Abdel Aziz (Journal of Applied Pharmaceutical Science, 2019)
An exopolysaccharide Exopolysaccharide (EPSNC2) produced from marine Streptomyces hirsutus NRC2018 which was isolated from marine sediments at North Coast, Egypt with accession number MK050544. EPSNC2 was a β-type heteropolysaccharide contained uronic acid (72.73%) with no sulfate groups and overall average molecular weight (Mw) 4.25×105 g/mol. The monosaccharide composition was glucuronic:galacturonic:glucose:mannose:arabinose with molar ratio 1.2:0.6:0.1:0.2:0.1, respectively. EPSNC2 was subjected to antioxidant, anticancer, and antiviral in vitro tests, showed high 1, 1-diphenyl-2-picrylhydrazyl free radical scavenging activity whereas, the maximum antioxidant activity was 95.9% at 1,500 µg/ml after 120 minutes and the IC50 value was 158.5 µg/ml. Also, EPSNC2 had the ability to scavenge H2 O2 and the maximum activity was 75.6% with an estimated IC50 value 501.2 µg/ml. Furthermore, EPSNC2 showed a reducing power activity as well as a metal chelating activity in a dose dependant manner and the activity reached 98.5% at 1,000 µg/ml. EPSNC2 had a significant and specific anticancer effect on CaCo-2 cell line without any effect on other cell lines and the IC50 was estimated to be 295.1 µg/ml. Our results regarding the antiviral activity against Herpes Simplex virus type 1 (HSV-1), Hepatitis A virus, and Coxsackie B-4 were 84.9%, 20.3%, and 45.4%, respectively at 125 µg/ml with no activity against adenovirus. Therefore, the EC50 value against the enveloped virus HSV-1 was 32.4 µg/ml.
Keywords: Exopolysaccharide, production, Streptomyces hirsutus, antioxidant, anticancer, antiviral.